Physical culture as a phenomenon of the development of socio-cultural competence of future teachers of physical education - I.V. Ivanii (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to substantiate the phenomenon of formation of physical culture of the individual in terms of theoretical and methodological approaches to the development of socio-cultural competence of future teachers. Material : 22 literary sources analyzed on the issue of formation of physical culture of the individual. Used cultural studies, axiological and competence approach. Results : define the concept of socio-cultural competence of the teacher of physical education. Competence is considered as an integrative motivational tumor - activity sphere of the individual. It determines the focus of an expert on the formation of spiritual values and is the foundation for its further self-development. Disclosed structure sociocultural competence of the teacher in the unity components: cognitive, motivational-value, behavioral. For each component defined system of spiritual values. The system covers the socio- psychological, mental and cultural values of physical culture. Conclusions : the sociocultural competence of the teacher of physical education meaningful and functionally related to the values of the physical culture of the individual. Spiritual, value the personality of the teacher - is the foundation for all of the components of socio-cultural competence. This competence provides social and cultural development of the individual.